COVID-19 and Internet Hospital Development in China - Yushan Li; Huimin Hu; Liudmila Rozanova; Guilhem Fabre (MDPI AG, 2022)
Since 2018, the access policy for Internet hospitals has been issued in China. So far, thousands of Internet hospitals have been approved to operate and have played a significant role during the COVID-19 pandemic. While front-line hospitals strive to treat patients, Internet hospitals take the responsibility to guide patients to seek appropriate medical treatment and meet the urgent needs of chronic patients through online medical follow-up, payment, and drug distribution. This paper is based on Internet medical policies and interviews with doctors working with Internet hospitals, aiming to study the development of Internet hospitals in China through the management of the COVID-19 outbreak and the Chinese healthcare strategy on the national level.